Analysis of Brute Force Attacks with Ylmf-pc Signature - Anton Valeryevich Arzhakov; Dmitry Sergeevich Silnov (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Brute force techniques used in many fields of authentication process. Ftp servers, web servers and mail servers very often got threatened by attackers. Old technique for mail service brute force still working and it can be easily detected by special signature.